Methodological procedures for priority setting mental health research: a systematic review summarising the methods, designs and frameworks involved with priority setting - Kris Deering; Neil Brimblecombe; Jane C. Matonhodze; Fiona Nolan; Daniela A. Collins; Laoise Renwick (BMC, 2023)
Abstract Background Research priority setting aims to identify research gaps within particular health fields. Given the global burden of mental illness and underfunding of mental health research compared to other health topics, knowledge of methodological procedures may raise the quality of priority setting to identify research with value and impact. However, to date there has been no comprehensive review on the approaches adopted with priority setting projects that identify mental health research, despite viewed as essential knowledge to address research gaps. Hence, the paper presents a summary of the methods, designs, and existing frameworks that can be adopted for prioritising mental health research to inform future prioritising projects. Method A systematic review of electronic databases located prioritisation literature, while a critical interpretive synthesis was adopted whereby the appraisal of methodological procedures was integrated into the synthesis of the findings. The synthesis was shaped using the good practice checklist for priority setting by Viergever and colleagues drawing on their following categories to identify and appraise methodological procedures: (1) Comprehensive Approach-frameworks/designs guiding the entire priority setting; (2) Inclusiveness -participation methods to aid the equal contribution of stakeholders; (3) Information Gathering-data collecting methods to identify research gaps, and (4) Deciding Priorities-methods to finalise priorities. Results In total 903 papers were located with 889 papers removed as either duplicates or not meeting the inclusion and exclusion criteria. 14 papers were identified, describing 13 separate priority setting projects. Participatory approaches were the dominant method adopted but existing prioritisation frameworks were modified with little explanation regarding the rationale, processes for adaptation and theoretical foundation. Processes were predominately researcher led, although with some patient involvement. Surveys and consensus building methods gathered information while ranking systems and thematic analysis tend to generate finalised priorities. However, limited evidence found about transforming priorities into actual research projects and few described plans for implementation to promote translation into user-informed research. Conclusion Prioritisation projects may benefit from justifying the methodological approaches taken to identify mental health research, stating reasons for adapting frameworks alongside reasons for adopting particular methods, while finalised priorities should be worded in such a way as to facilitate their easy translation into research projects.